2016
DOI: 10.1177/0271678x16642443
|View full text |Cite
|
Sign up to set email alerts
|

Risk of long-term anticoagulation under sustained severe arterial hypertension: A translational study comparing warfarin and the new oral anticoagulant apixaban

Abstract: New oral anticoagulants for the prevention of stroke and systemic embolism in patients with atrial fibrillation have recently been introduced. In this translational study, we explored the risk of long-term anticoagulation on intracerebral hemorrhage under sustained severe arterial hypertension. We initiated anticoagulation with warfarin or apixaban in spontaneously hypertensive rats prone to develop severe hypertension and subsequent intracerebral bleeding complications. A non-anticoagulated group served as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…On the clinical side, INTERACT II reported a strong trend towards a benefit of the intervention whereas ATACH II reported neutral or even worse outcomes. 1,2 The ani-mal data in contrast affirms that blood pressure reduction translates into a better functional outcome. In fact, in the ATACH II trial more complications occurred in the intensively treated group such as increased frequency of kidney failure.…”
Section: Dear Sirmentioning
confidence: 98%
See 4 more Smart Citations
“…On the clinical side, INTERACT II reported a strong trend towards a benefit of the intervention whereas ATACH II reported neutral or even worse outcomes. 1,2 The ani-mal data in contrast affirms that blood pressure reduction translates into a better functional outcome. In fact, in the ATACH II trial more complications occurred in the intensively treated group such as increased frequency of kidney failure.…”
Section: Dear Sirmentioning
confidence: 98%
“…1 The Intensive Blood Pressure Reduction in Acute Cerebral Hemorrhage Trial II (INTERACT II) study revealed a strong tendency towards improved outcomes in ICH patients subjected to intensive blood pressure lowering, 1 while the Antihypertensive Treatment of Acute Cerebral Hemorrhage Trial II (ATACH II) trial reported worse outcomes. 2 So far, the pathophysiologic consequences of intensive blood pressure lowering in acute ICH are scarcely understood. Here we describe an experimental model with translational reference to the INTERACT II and ATACH II trials.…”
Section: Dear Sirmentioning
confidence: 99%
See 3 more Smart Citations